2018
DOI: 10.1108/ijphm-07-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and satisfaction at the hospital

Abstract: Purpose This study aims to compare public and private hospitals based on both cognitive and affective components of patients’ satisfaction. Design/methodology/approach A survey of 770 Italian patients from public and private hospitals was conducted. Then, hierarchical and non-hierarchical cluster analyses and a series of chi-squared tests were run with the aim of segmenting patients’ emotional response. Findings Respondents show different levels of satisfaction and a different emotional status based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 69 publications
4
9
0
Order By: Relevance
“…Indeed, enthusiastics showed higher positive emotions (i.e., fun, interest, satisfaction, pride, cheerfulness, pleasure, and joy). This result seems to confirm previous studies that reported a direct relationship between positive emotions and behavioural intentions of heritage tourists (Prayag, Hosany, Muskat, & Del Chiappa, 2017;Prayag, Hosany, & Odeh, 2013) and, more broadly, that found emotions adequate for consumer segmentation (Bigné & Andreu, 2004;Del Chiappa et al, 2014;Pinna, Del Chiappa, & Atzeni, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, enthusiastics showed higher positive emotions (i.e., fun, interest, satisfaction, pride, cheerfulness, pleasure, and joy). This result seems to confirm previous studies that reported a direct relationship between positive emotions and behavioural intentions of heritage tourists (Prayag, Hosany, Muskat, & Del Chiappa, 2017;Prayag, Hosany, & Odeh, 2013) and, more broadly, that found emotions adequate for consumer segmentation (Bigné & Andreu, 2004;Del Chiappa et al, 2014;Pinna, Del Chiappa, & Atzeni, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…This resonates with marketing, design and health informatics scholarship that identifies the way that certain scenic arrangements, such as the type and color of health tools (Hopkin et al. , 2019), the spaciousness and traffic flow of hospital spaces (Pinna et al. , 2018), or the placement of computers in courtrooms (Bens, 2018), affect the emotions of participants enough to play a role in their decision-making.…”
Section: Theorizing Goffmanian Performances Of Professional Controlmentioning
confidence: 88%
“…In-person, these symbols come together to form an ambience, a cultural milieu, in which they are experienced through relationally constructed desires that provide not only sensory pleasure and variety, but access to a luxurious lifestylea higher-status in-group into which elective cosmetic surgery is portrayed as a gateway. This resonates with marketing, design and health informatics scholarship that identifies the way that certain scenic arrangements, such as the type and color of health tools (Hopkin et al, 2019), the spaciousness and traffic flow of hospital spaces (Pinna et al, 2018), or the placement of computers in courtrooms (Bens, 2018), affect the emotions of participants enough to play a role in their decision-making. Symbolism and ambience are strategies of developing luxurious projections that become part of the meanings that consumers associate with cosmetic surgery, but also help to develop expectations of service, rather than of membership in a higherstatus in-group.…”
Section: Consumer Logics and High-risk Goodsmentioning
confidence: 89%
“…Low quality of service is a major source of dissatisfaction. Consumers who intend to purchase health insurance policies expect better service quality (Bala et al, 2011;Agyapong et al, 2017;Ameryoun, 2017;Pathak, 2018;Pinna et al, 2018;Batbold and Pu, 2021) . The nature of service quality will ultimately influence customer satisfaction (Rajamani and Raj, 2021) .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted regarding factors that influence the intention to pay insurance contributions, such as health services, with the object of research being health services in hospitals (Bala et al, 2011;Ahmad et al, 2012;Agyapong et al, 2017;Pathak, 2018;Pinna et al, 2018) . Furthermore, there is also research related to health insurance services (Nosratnejad et al, 2016;Hajek et al, 2020;Wu et al, 2020;Batbold and Pu, 2021) .…”
Section: Introductionmentioning
confidence: 99%